(untitled) (Journal of Engineering, 2006)
Many researchers recommended Falling Weight Deflectometer (FWD) to be use for the purpose of stiffness profile determination of existing pavement. Several sources of uncertainties contribute to the inaccuracies in moduli obtained in this manner. these include: 1) the measured parameters (deflection basin and FWD load), 2) the back calculation model, and 3) the pavement parameters, such as Poisson’s ratio and thickness of each pavement layer . In the present study the influence of the variation in the thickness and other pavement parameters on the backcalcuted moduli are investigated .Theoretical deflection basins were generated for different pavement structure using program Mich-pave. Mich-back program was then utilized to backcalculate the moduli from these theoretical basins. To assess the influence of the variability in thickness, Poisson’s ratio, FWD load and deflection, a Monte Carlo simulation process was employed. Results show that the backcalculation of the layer moduli is greatly influence by the variability of the combined pavement. A sensitivity analysis showed that the uncertainties in thicknesses are the major contributor to variations of the backcalculated Moduli.